COAST, LOWLAND, AND HIGHLAND: A GEOGRAPHICAL UNITY IN SUPPORTING THE ECONOMY OF CIREBON FROM XIX-XX CENTURY - Eva Nur Arovah; Nina Herlina Lubis; Reiza Dienaputra; Widyo Nugrahanto (Paramita: Historical Studies Journal)
Since 14th and 15th century, the kingdoms located among the islands of archipelago, including Cirebon, have involved in trading activities among the islands of archipelago or even international. Started from the fall of Majapahit and Demak kingdoms, the northern coastal areas of Java mostly are dominated by the rulers and Moslem traders. In 17th century, by the equal disintegration of traditional politics and taking over of the power of Cirebon Palace by VOC and the system and direction of policy which are made by the Dutch government, the sector-based trade in the coastal area of Cirebon becomes increasingly advanced and widespread. Started from the coastal area, in its development, the developing center trade becomes in hand with the developing of agricultural sectors in the lowlands and plantation in the highlands. By the historical method and structural approach from Fernand Braudel, this research is trying to explain Cirebon’s Geography as a synthesis that plays a role in Cirebon economic activity. No less important, archaeological evidences will be included as an attempt to identify the historical fact. Because in reality, the three regions (coastal area, agriculture and plantation) are a unity of the mutually bounded and have a reciprocal relationship in its contribution to the economic progress of the Dutch.